A single electron nanomechanical Y-switch - Kim, Chulki; Kim, Hyun-Seok; Prada, Marta; Blick, Robert H. (ROYAL SOC CHEMISTRY, 2014)
We demonstrate current switching in the frequency domain using a nanomechanical shuttle with three terminals operating at room temperature. The shuttle consists of a metallic island on top of a Si nanopillar forming the Y-junction. A flexural mode of the nanopillar is excited by applying an external bias to one of the contacts, allowing electrons to be shuttled across the oscillating island.